Steady formation analysis on multi-robot systems. Issue 1 (2nd January 2017) - Liu, Yutong; Yu, Hongjun; Lim, Cheng-Chew; Shi, Peng
Abstract : In this paper, a controller is designed for a group of cooperative robots to achieve the stable displacements. Communication network among the robots is assumed unavailable and each robot can only measure the displacements relative to their neighbours. The controller will enable the robots to move to a predefined formation or a special formation under a suitable protocol which we will design. We will discuss the effect of different sizes of the multi-vehicle system and conduct simulations to verify the effectiveness of the proposed controller and the formation protocols.